Trust, Corruption, Bribes and Economic Development in Central and Eastern European Countries - Ana Iolanda Voda; Claudiu Tiganas; Dumitru Filipeanu (CES Working Papers, 2013)
The evolution of the Western world has drawn on theoretical structures of classical and neoclassical liberalism for its explanatory support and sources of inspiration for centuries. Against this ideological background, institutionalists aim at showing that growth is a process of transformation, a double change: an economic and an institutional one. In this analysis, our purpose is to highlight the importance of informal institutional arrangements and their quality in explaining the disparities of revenues and developments between countries. In our approach, we will consider several indicators meant to highlight various aspects of research. The approach proposed is a transversal-comparative one and static methods pertain to uni- and multivariate analysis. The results obtained suggest the existence of major differences within the Central and East European area as far as informal institutions are concerned; moreover, the analysis conducted confirms the existence of a significant relation between the level of development and the structure of informal arrangements such as: trust level, bribe culture and corruption control.
Keywords: K42; O17; 330; institutions; trust; corruption; bribes; development Romania